Earthquake clusters in NW Peloponnese. - Mesimeri, M.; Papadimitriou, E.; Karakostas, V.; Tsaklidis, G. (Bulletin of the Geological Society of Greece, 2013)
Clusters commonly occur as main shock – aftershock (MS-AS) sequences but also as earthquake swarms, which are empirically defined as an increase in seismicity rate above the background rate without a clear main shock. A delcustering algorithm is employed to identify clusters from a complete catalog of earthquakes that occurred in the area of NW Peloponnese (Greece) during 1980-2007. In order to distinguish these clusters we calculate the skewness and kurtosis of seismic moment release for each cluster, since swarm-like sequences generally have lower skew value of moment release history than MS-AS. The spatial distribution of b-value was calculated for the entire catalog as for the declustered one, in order to correlate them with seismicity behavior of the region. Finally, the pre-stress field of Achaia 2008 earthquake was calculated aiming to associate the stress accumulation with the occurrence of the identified clusters